Downregulation of the Yes-Associated Protein Is Associated with Extracellular Matrix Disorders in Ascending Aortic Aneurysms - Haiyang Li; Wenjian Jiang; Weihong Ren; Dong Guo; Jialong Guo; Xiaolong Wang; Yuyong Liu; Feng Lan; Jie Du; Hongjia Zhang (Stem Cells International)
Previous studies indicate that extracellular matrix (ECM) disorders lead to the apoptosis of Vascular Smooth Muscle Cells (VSMCs), which impairs the aortic wall by reducing the generation of elastic fibers, and ultimately result in ascending aortic aneurysm. The critical role of the Yes-associated protein (YAP) has been elucidated in cardiac/SMC proliferation during cardiovascular development. However, the association of YAP expression and extracellular matrix disorders in ascending aortic aneurysms is not clear. Here, we present for the first time that the downregulation of YAP in VSMCs is associated with ECM disorders of the media in ascending aortic aneurysms. We found that aortic ECM deteriorated with increased apoptotic VSMCs. Moreover, expression of YAP was dramatically reduced in the aortic walls of patients with ascending aortic aneurysms, while the normal aortic samples exhibited abundant YAP in the VSMCs. These results suggest that downregulation of YAP leads to apoptosis of VSMCs, which are essential for the homeostasis of the aortic wall. The resultant ECM disorders affect aortic structure and function and contribute to the development of ascending aortic aneurysms. In summary, through assessment of clinical samples, we revealed the association between downregulation of YAP in VSMCs and the development of ascending aortic aneurysms, providing new insight into the pathogenesis of this disease.